Neurochemical effects of the monoamine oxidase inhibitor phenelzine on brain GABA and alanine: A comparison with vigabatrin - Kathryn G. Todd; Glen B. Baker (Frontiers Media S.A., 2008)
PURPOSE. To compare phenelzine (PLZ), an antidepressant drug with anxiolytic properties which inhibits monoamine oxidase (MAO) but also elevates rat brain levels of the amino acids ?-aminobutyric acid (GABA) and alanine (ALA), with vigabatrin (VIG), an anticonvulsant which elevates brain GABA by inhibition of GABA transaminase (GABA-T), with regard to their actions on brain levels of GABA and ALA and on activities of MAO, GABA-T and ALA transaminase (ALA-T). METHODS. Male rats were administered PLZ (10 mg/kg) or VIG (1,000 mg/kg) i.p., and the rats were euthanized 4 hours later and the brains removed for analysis of levels of GABA and ALA (by electron capture gas chromatography after derivatization) and activities of MAO, GABA-T and ALA-T (radiochemical assays). RESULTS. Both PLZ and VIG inhibited GABA-T and elevated GABA levels. Only PLZ inhibited MAO and ALA-T and elevated ALA levels. The effects of PLZ on both amino acids and their transaminases were blocked by pre-treatment with the MAO inhibitor tranylcypromine. This pretreament had no effect on the inhibition of GABA-T or the elevation of brain GABA levels produced by VIG. CONCLUSIONS. At the doses studied, PLZ was as effective as VIG at elevating brain GABA levels, but, unlike VIG, also inhibited MAO and ALA-T (and increased brain ALA levels). Pretreatment of rats with the MAO inhibitor tranylcypromine prevented the increase in brain GABA and ALA levels with PLZ, but did not block the effect of VIG on GABA. These observations with tranylcypromine and PLZ support the hypothesis that an active metabolite of PLZ produced by the actions of MAO on this drug plays a major role in its GABA- and ALA-elevating actions.